2016
DOI: 10.5897/ajar2015.10758
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen compounds, proteins and amino acids in corn subjected to doses of aluminum

Abstract: Corn (Zea mays L.) is highly adaptable, but it has difficulties in expressing its productive potential in soils with high aluminum content, since this element is directly related to high acidity in the soil. The objective of this study was to evaluate the nitrogen compounds, proteins and amino acids of two corn cultivars subjected to increasing doses of aluminum. The experiment was carried out in a greenhouse using one of the corn plants from varieties BRS 106 and BRS 4157. The experimental design was entirely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Another researches clearly demonstrate that the upatake capacity and incorporation of N in organic molecules are impaired in plants exposed to Al 3+ ; for instance, the effect of Al 3+ on nitrate reduction was observed by Cruz et al (2011) and Souza et al (2016), in sorghum and maize, respectively; and this has led to drastic decreases in plant growth capacity. This response is directly related to the role of N in plant growth; nitrate reduction is the first step of the N-NO3pathway and takes place in the cytosol; and then, the nitrite is transported to the plastids to be reduced to ammonia that it promptly protonated to ammonium which is incorporated in carbon skeletons via GS/GOGAT pathway (Masclaux- Daubresse et al 2010).…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Another researches clearly demonstrate that the upatake capacity and incorporation of N in organic molecules are impaired in plants exposed to Al 3+ ; for instance, the effect of Al 3+ on nitrate reduction was observed by Cruz et al (2011) and Souza et al (2016), in sorghum and maize, respectively; and this has led to drastic decreases in plant growth capacity. This response is directly related to the role of N in plant growth; nitrate reduction is the first step of the N-NO3pathway and takes place in the cytosol; and then, the nitrite is transported to the plastids to be reduced to ammonia that it promptly protonated to ammonium which is incorporated in carbon skeletons via GS/GOGAT pathway (Masclaux- Daubresse et al 2010).…”
Section: Resultsmentioning
confidence: 91%
“…Regarding N nutrition, some studies revealed that nitrate uptake is impaired in the presence of Al 3+ in commercial cultivars of sorghum (Cambraia et al 1989). In a similar and more recent study, Souza et al (2016) demonstrated in maize that Al 3+ affected several pathways of N assimilation, including decreasing nitrate reductase enzyme activity. These data show that a satisfactory production is beyond just supply fertilizer.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…In the same way it was noticed that AA primed RD2052 showed 42.15% increased, while RD2552 AA primed showed 26.63% increase, similarly SA primed RD2052 showed 38.86% increase, while SA primed RD2552 showed 20.33% increase at 6mM Aluminum concentration compared to control. According to Luma et al, (2016) increased in total soluble amino acid content may have probably been caused by the increase in the activity of proteases enzyme, which break the reserve proteins according to the exposition of a plant to any injury, in this case the effect of aluminum toxicity. Treatment with AA and SA less increased concentration of free amino acid was noticed compared to unprimed variety.…”
Section: Resultsmentioning
confidence: 99%
“…The root tip is the first tissue to contact and feel the aluminum toxicity [8]. A large number of experiments have shown that aluminum toxicity can inhibit the growth and division of root cells, thereby affecting the absorption of water and nutrients [9], such as rice [10], maize [11], and tea plant [12]. Meanwhile, aluminum toxicity will break the original balance of physiological reactions in plants, promotes excessive accumulation of active oxygen, and causes oxidative stress in plants [13,14].…”
Section: Introductionmentioning
confidence: 99%